The Shackles of Rice Farmers' Dependence On The Deadline For The Study Of Islamic Business Ethics Perspectives - Jazuli, Jazuli; Djalaluddin, Ahmad; Kamayanti, Ari (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This study examines the role of middlemen in the distribution of agricultural products in Curahdami Village, Bondowoso Regency, and explores the application of Islamic business ethics in their practices. The findings of the study suggest that middlemen play an important role in facilitating market access for farmers, although their business practices are often characterized by price injustice and manipulation of product quality. This study uses a qualitative approach, by recommending several measures to improve justice and sustainability in the practice of squatting, including ethical education for farmers and middlemen, the establishment of agrarian cooperatives to strengthen farmers' bargaining power, local regulations to prevent exploitative practices, and the strengthening of social capital through community forums. These measures are expected to create a fairer distribution system and improve the welfare of farmers in the long run.